A Multidisciplinary Team Approach to the Treatment of Liver Cirrhosis - Zhang YR; Wang H; Zhou N; Zhang YD; Lin Y; Wu LY; Wei SF; Ma YY; Wang CX (Dove Medical Press, 2021)
Yue-Rong Zhang,1 Hui Wang,2 Ning Zhou,2 Yao-Di Zhang,1,2 Yan Lin,1,2 Li-Yang Wu,1,2 Shi-Fang Wei,2 Yan-Yun Ma,2,3 Chun-Xia Wang3 1Department of Gastroenterology, University-Town Hospital of Chongqing Medical University, Chongqing, People's Republic of China; 2Department of Infectious Diseases, The First People's Hospital of Lanzhou, Gansu, 730050, People's Republic of China; 3Department of Laboratory, The First People's Hospital of Lanzhou, Gansu, 730050, People's Republic of ChinaCorrespondence: Yue-Rong ZhangDepartment of Gastroenterology, University-Town Hospital of Chongqing Medical University, No. 55 University Town Middle Road, Shapingba District, Chongqing, 401331, People's Republic of ChinaTel/Fax +86 102365714142Email zhang_yue_rong@163.comObjective: To explore the feasibility of treating cirrhosis using a multidisciplinary team approach (MDT) and to pinpoint the key factors influencing its implementation.Methods: The data of 307 patients with decompensated cirrhosis were studied retrospectively. Patients who received more than two treatment measures were assigned to the MDT group (n=228), and patients who received symptomatic medical drug treatment only were assigned to the traditional treatment group (n=79). The follow-up period ranged from 4 to 10 years, and the average follow-up period was 5.7 years. The results of the biochemical tests for hepatitis B virus deoxyribonucleic acid, hepatitis C virus ribonucleic acid, and autoantibodies to liver disease were analyzed.Results: The differences in gender and Child-Pugh grade of liver function between the two groups were not statistically significant. The MDT group had obvious advantages over the traditional treatment group in occupational composition, etiology composition, 5-year survival rate and annual hospitalization times. The leading causes of death in the MDT group, in descending order, were liver cancer, infection, mesenteric thrombosis, and non-hepatic disease, and, in the medical treatment group, they were liver failure, gastrointestinal bleeding, infection, and liver cancer. There was a significant statistical difference between the two groups (p < 0.05). In the multidisciplinary treatment, etiological treatment was the most widely used treatment, accounting for 79.8%, followed by endoscopic treatment (33.3%), peritoneal drainage and ascites reinfusion (25%), splenectomy combined with devascularization (11.4%) and stem cell transplantation and liver transplantation (1.8%).Conclusion: An MDT can improve the efficacy and prognosis of patients with cirrhosis and improve patient compliance. After multi-disciplinary intervention, the mortality spectrum of long-term survival patients with cirrhosis changes, and the mortality rate of liver cancer and non-liver disease increases.Keywords: liver cirrhosis, decompensated period, multidisciplinary team mode, traditional treatment, retrospective study